Pengaruh Motivasi, Iklim Kerja, dan Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru SD Kecamatan Mesuji OKI - Tyagita Manggiasih Windari; Tri Widayatsih; Suherman Suherman (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to determine the influence of teacher work motivation, work climate, and principal leadership on the performance of public elementary school teachers in Mesuji District, Ogan Komering Ilir Regency. The type of research used in this study is descriptive research, namely research that aims to describe or explain something according to reality. The approach used in this study is quantitative, namely research that focuses more on the accuracy of the description of each variable and the accuracy of the influence between one variable and another. This research was conducted in Mesuji District, Ogan Komering Ilir Regency, with the subjects of this research being teachers of Public Elementary Schools conducted in Mesuji District, Ogan Komering Ilir Regency with a sample size of 63 respondents. The data used were data from questionnaires and interviews. For the questionnaire instrument trial, a trial was conducted on teachers at four schools in Mesuji District: SDN 1 Pematang Panggang, SDN 2 Pematang Panggang, SDN 1 Sido Basuki, and SDN 1 Pematang Bongor. The validity and reliability were then analyzed using the Statistics Product and Service Solution (SPSS) version 17.0 application. From the multiple linear regression test using the SPSS version 17.0 application on the questionnaire results, it was found that there was a positive relationship between the independent variables, namely work motivation, work climate, principal leadership, and the performance of state elementary school teachers in Mesuji District, Ogan Komering Ilir Regency. The results of the determination coefficient test show that teacher performance can be explained by the variables of teacher work motivation (X1), work climate (X2) and principal leadership (X3) by 65.6%. While the remaining 34.4% of teacher performance (Y) can be explained by other variables that are not studied. As a conclusion of this study is that there is a significant positive influence between teacher work motivation, work climate and principal leadership on teacher performance in the teaching and learning process at Public Elementary Schools in Mesuji District, Ogan Komering Ilir Regency.